Maternal and Neonatal Outcomes of Syrian Adolescent Refugees and Local Adolescent Turkish Citizens: A Comparative Study at a Tertiary Care Maternity Hospital in Türkiye - Ceren Golbasi; Tayfun Vural; Burak Bayraktar; Hakan Golbasi; Alkim Gulsah Sahingoz Yildirim (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aim to compare the maternal and obstetric outcomes between local adolescent Turkish citizens and adolescent Syrian refugees admitted to a tertiary care center in Turkey.